Language teacher metacognition: beyond the mirror. Issue 1 (1st January 2021) - Hiver, Phil; Whiteside, Zach; Sánchez Solarte, Ana C.; Kim, Claudia J.
ABSTRACT: In language teaching, current understanding of complex classroom contexts and post-methods L2 pedagogy encourages us to adopt a situated and dynamic perspective of the language classroom. Exemplary teaching in such contexts is characterized by critical moment to moment decision-making for building L2 classroom environments that are engaging, demanding, and supportive of learners' development. Parallel to this, the notion of teacher reflection (aka. reflective practice) has gained considerable momentum in the field, evidenced by existing work on the topic and its continued popularity in scholarship on language teachers. However, a review of this topical area reveals inconsistencies and unresolved dilemmas, suggesting that notions of teacher reflection and reflective practice in our field are ripe for reconceptualization. In response, we propose that the field of L2 teaching adopt the superordinate notion of teacher metacognition in order to better address the links between language teachers' inner worlds, their classroom teaching, and students' learning. We discuss the implications of adopting a perspective that is informed by current evidence in teacher education research and the learning sciences for understanding the interface between teacher thought and action, and students' development.